Elicitation of Health-related Quality-of-life Concepts Associated with Overactive Bladder: A Qualitative Study - Natalia Hawken; Zalmai Hakimi; Samuel Aballéa; Jameel Nazir; Isaac A. O. Odeyemi; Mondher Toumi (Journal of Health Economics and Outcomes Research, 2016)
# Background Overactive bladder (OAB) is a symptom-defined disorder. A range of instruments are available for assessing OAB symptom bother, urinary urgency and the effects of symptoms on health-related quality of life (HRQoL), but few have been specifically designed and validated for this condition. HRQoL instruments should capture the concepts that are most relevant to patients. To our knowledge, there is no existing published conceptual framework for OAB.